What time is it?... The pedagogical press section in Repertorio Americano. An approach - Cascante Gómez, Lode Elena (2021)
Repertorio Americano magazine , edited by Joaquín García Monge, is a valuable means of cultural diffusion and also Latin American and Costa Rican political thought. Different problems are discussed and those related to education are numerous either in quality, authors or subjects throughout the life of the magazine. However, its analysis from the perspective of a place for the diffusion of pedagogical ideas has not yet been done. As a result, this article presents an approach to ¿What time is it?... section as a space for formal pedagogical publications that explain different views on Hispanic American thought from the first half of the 20th century.